Spatially-explicit effects of seed and fertilizer intensification for maize in Tanzania - Komarek, Adam M.; Koo, Jawoo; Wood-Sichra, Ulrike; You, Liangzhi (Elsevier, 2018)
Our simulation study examined the productivity and economiceﬀects of planting diﬀerent seed cultivars and increasing fertilizer application rates at multiple spatial scales formaize in Tanzania. We combined crop simulation modelling with household data on costs and prices to examineﬁeld-scale and market-scale proﬁtability. To scale out our analysis from the ﬁeld scale to the regional andnational scale (market scale) we applied an economic surplus model.